Influence of stress ratio on residual stress evolution near cold-expanded hole due to low-cycle fatigue by crack compliance data (Fracture and Structural Integrity, 2020)
Modified version of the crack compliance method is used for determination of stress intensity factor (SIF) related to narrow notches emanating from cold-expanded holes. These notches are inserted at different stages of low-cycle fatigue under constant external load. It is shown how residual SIF values, generated by residual stress field influence, can be separated from total experimental SIF values. Residual SIF values, obtained at different stage of low-cycle fatigue with the same stress range Δσ  = 350 MPa but different stress  R = –0.4 and  R = –1.0, provide quantitative description of residual stress evolution near cold-expanded hole. It shown that maximal residual stress relaxation of order 20 per cent occurs at 95 lifetime per cent for both loading programs.
Keywords: Metal-composite joints; Cold hole expansion; Residual stress intensity factor; Residual stress